Deissi, riferimento, metafora Questioni classiche di linguistica e filosofia del linguaggio - Keidan, Artemij; Alfieri, Luca (Studi e saggi, 2008)
This collection of essays by young specialists in linguistic disciplines addresses the oldest - and yet still topical - issues in the debate on language. It also includes a contribution by the famous Russian semiologist Boris Uspenskij (pupil, friend and collaborator of L. Hjelmslev, R. Jakobson and M. Lotman). Valentina Martina explores the relation between the plane of linguistic meanings and reality through an analysis of the concept of "system". The article by Artemij Keidan addresses the problem of the definition of deixis and its role in the disambiguation of proposition, with special reference to structuralism and contemporary theories on direct reference. The work of Luca Alfieri takes its cue from recent studies on cognition to demonstrate the unsustainability of the Jacobsonian dichotomy of metaphor and metonymy. Rounding off the book is an essay by Boris Uspenskij on the role of personal pronouns in the structure of language, in semiotics and in human communication, lavishly illustrated with examples and historical curiosities.